Premarital Sexual Behavior of Boarding Students in Makassar City - Andi Chaerul; Yusriani; Andi Nurlinda (Science Midwifery, 2022)
Premarital sex is one of the most complex adolescent problems. Universities that are far from home, make female students have to rent temporary housing which results in a lack of supervision from parents, and increasingly free association can exacerbate sexual behavior in female students. This type of qualitative research with a quasi-qualitative approach. Determination of informants by a snowball with a total of 7 informants. The result of the study is that the main cause of premarital sex occurs because self-control then lifestyle, religious understanding, parental relationships, and the media also encourage premarital sex. The premarital sex behavior of female students is very vulnerable. The intensity of sexual intercourse is quite intense, they do not use contraception and they have premarital sex in boarding houses, in hotels, and even in private homes. The impact of premarital sex on teenagers or college students is that they experience a psychological impact, namely regret, but feelings have already made them keep doing it.